Logo instytucji non profit – modele stosowane w bibliotekach - Kruszewski, Tomasz (Biblioteka Uniwersytecka w Poznaniu, 2011)
W artykule scharakteryzowano znaki graficzne współczesnych bibliotek, które są używane w procesie identyfikacji wizualnej. Logo poszeregowano według zaproponowanych przez autora typów, co pozwoliło na wyłonienie najczęstszych tematów podejmowanych przy ich opracowywaniu. Zbytnie podobieństwa powodują kłopoty z określeniem tożsamości biblioteki. Wskazano, że jednym ze środków pozwalających na uniknięcie trudności identyfikacyjnych jest stosowanie abstrakcyjnych znaków graficznych, których kilka egzemplifikacji podano na końcu artykułu.

This article presents some selected issues on the characteristics of graphic marks used by modern libraries as logos that are intended to appeal to the target audience as both a trademark and a symbol of quality. However, in practice, theoretical assumptions and guidelines are often not taken into account. This is often the case in a situation where there are many similar institutions operating on the market and offering similar services. Libraries are a good example of this phenomenon. Logos of libraries (mainly those of national and public libraries) tend to copycat whatever the going trend is in the design of graphic signs, but also in common errors, and repeated patterns. Similarities in form and substance behind a logo blur the identity of a given library. In conclusion, the author postulates to increase the quality and the diversity of new logos to be used in various non-profit institutions.
The logo of the non-profit institution – a sample model for libraries
Keywords: logo; branding biblioteki; library branding; identyfikacja wizualna; corporate design; tożsamość firmy; corporate identity